The Value-Added Tax Paradox of Foreclosed Collateral (AYDA) in Option-to-Purchase Finance Leases - Gumelar, Achmad; Yanti, Harti Budi (E-Jurnal Akuntansi, 2025)
This article investigates the conflicting value added tax (VAT) treatments applied to agunan yang diambil alih (AYDA, or foreclosed collateral) when it serves as security for (i) conventional credit facilities and (ii) finance -lease contracts that include an option to purchase. Under Minister of Finance Regulation No. 41/2023 (MoFR 41/2023), finance companies initially imposed a concessional 1.2 percent VAT on AYDA disposals. A subsequent tax-ruling response (Letter No. S-819/KPP.3011/2024), however, drew a sharp distinction: the 1.2 percent rate applies only when the collateral is legally owned by the debtor, whereas repossessed lease assets—held in the lessor’s name—must be taxed at the full 12 percent statutory rate. This divergence has created material compliance uncertainty, increased exposure to administrative penalties, and threatened the cost structure of finance companies that rely heavily on lease financing. Employing a comparative doctrinal analysis of the statutory texts, supplemented by interpretive case studies from leading finance companies, the study maps the sources of interpretive error and quantifies the attendant VAT-compliance risks. The evidence underscores the need for clearer regulatory guidance and harmonised tax policy to prevent mismatches between leasing practice and VAT law. Based on these findings, the paper formulates actionable recommendations for regulators and practitioners aimed at reducing tax-compliance costs, safeguarding operational sustainability, and reinforcing financial-sector stability. Keywords: VAT Rate for AYDA; VAT of sales of Foreclosed Asset; VAT of Foreclosed Asset; MoFR 41 2023